2015
DOI: 10.1007/s12282-015-0600-4
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence following treatment for breast cancer with an endoscopic nipple-sparing mastectomy

Abstract: E-NSM is an oncologically safe procedure and an acceptable method in selected patients requiring a mastectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Endoscopic breast surgery is a novel surgical method that uses a small incision wound to perform a complete resection of breast tissue. Many studies have shown that the oncological safety of endoscopic mastectomy is adequate relative to traditional operation methods [ 5 , 7 – 9 ]. In our previous study from the Taiwan Endoscopic Breast Surgery Cooperative Group database, the recurrence rate was about 1% for patients who had received a unilateral total mastectomy, supporting the safety of endoscopic surgery for breast cancer [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic breast surgery is a novel surgical method that uses a small incision wound to perform a complete resection of breast tissue. Many studies have shown that the oncological safety of endoscopic mastectomy is adequate relative to traditional operation methods [ 5 , 7 – 9 ]. In our previous study from the Taiwan Endoscopic Breast Surgery Cooperative Group database, the recurrence rate was about 1% for patients who had received a unilateral total mastectomy, supporting the safety of endoscopic surgery for breast cancer [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of an endoscopic technique in performing NSMs for cancer patients has also been described by Sakamoto et al (59,60) from Japan who uses a combination of an axillary and periareolar incision to perform the dissection off of the pectoralis fascia and the anterior skin flaps, respectively. The axillary incision is first used for the SLN biopsy.…”
Section: Discussionmentioning
confidence: 97%
“…In total, 22 studies [31][32][33][34][35][36][37][38]42,[47][48][49]54,55,57,[59][60][61]64,[66][67][68] reported local recurrence after immediate implant-based post-mastectomy breast reconstruction (I-IBR) (Fig. 3A, I 2 = 42.1% [95% CI, 3.8%-65.1%]).…”
Section: Immediate Versus Delayed Implant-based Pmbrmentioning
confidence: 99%
“…The weighted average proportion of local recurrences was 0.03 (95% CI, 0.02-0.04). Proportions of regional recurrences after I-IBR were reported in 10 studies 31,[33][34][35]38,48,55,57,60,66 (I 2 = 61.2% [95% CI, 22.6%-80.5%]), including 79 regional recurrences in 2446 patients (3.2%) (Fig. 3B; Table S3b).…”
Section: Immediate Versus Delayed Implant-based Pmbrmentioning
confidence: 99%
See 1 more Smart Citation